Expressão de Indoleamina 2,3-dioxigenase (IDO) durante o processo de fibrogênese renal e efeitos de sua inibição na transição epitélio mesenquimal induzida por TGF-β1 - Matheus, Luiz Henrique Gomes (2016)
Chronic kidney disease (CKD) is a worldwide highly prevalent and progressive disease. Its prevalence has doubled in the last decade and, as such, deserves attention and concern in the search for greater knowledge about its mechanisms. Renal fibrosis is an event that occurs in CKD and is characterized by an extensive inflammatory process with extensive macrophage migration and extracellular matrix accumulation, which may cause damage to the kidney architecture and renal function, and aggravating the condition of the patient. Indoleamine 2,3-dioxygenase (IDO) is an immunomodulatory molecule which has been implicated in various biological processes. Although the IDO has been associated with some kidney diseases, their role in renal fibrosis, is still unclear. Because IDO can be modulated by TGF-β1, a powerful pro-fibrotic molecule, there is the hypothesis that IDO may be involved in renal fibrosis particulary acting in the tubular epithelial-mesenchymal transition (EMT) induced by TGF-β1. Thus, the expression and activity of IDO in this study was analyzed using a model of renal fibrogenesis. Furthermore, the effect of inhibition of IDO by 1-methyl-tryptophan (MT) in the EMT induced by TGF-β1 was evaluated using tubular culture cells. Male Wistar rats were subjected to 7 days of unilateral ureteral obstruction UUO. Not obstructed kidneys from animals that UUO (CL) and SHAM rat kidneys were used as controls. Increased Interstitial collagen deposition was significant in obstructed kidneys (13.4% ± 2.6% in UUO versus 0.3% ± 0.1% in SHAM and 0.9% ± 0.1% in CL; p<0.0001). Immunohistochemical analysis revealed a significant increase in the number of macrophages in UUO kidneys(75.2 ± 12.6 cells/field in UUO versus 6.2 ± 0.8 cells/field in SHAM and 16.0 ± 2.7 cells/field in CL, p<0.0001), accompanied by reduction in tubular E-cadherim expression(20.8  5.4 in SHAM, versus 21.1  11.6 in CL and 2.7  1.1 in UUO). The markers of mesenchymal cells (alphaSMA and vimentin) were increased in UUO kidneys, particullary in renal interstitium (αSMA: 17.7  7.1 in SHAM, versus 74.5  23.5 CL and 368.8  45.8 ‡ (p<0.0001)(Vimentin: 13.0  0.9 in SHAM, versus 17.0  1.2 in CL and 141.3  8.8 ‡* (p<0.0001) * and tubules(αSMA: 27.2  6.5 SHAM, 35.8  0.90CL and 61.4  4.2 †*( (p<0.001)**OUU. These results characterize the process of epitelial to mesenchymal transition and were accompanied by increase of the TGF-beta1 expression (qRT-PCR)(relative expression. of 14.7 ± 0.1 in UUO versus 1.0 ± 2.2 in SHAM; p <0.0001). IDO was clearly expressed in the cortical and medullary tubules of the UUO kidneys. In addition, the activity of IDO was analyzed from kidney tissue, being significantly higher in UUO kidneys(19.9 ± 3.6% in UUO versus 5.0 ± 3.4% in SHAM and of 10.8 ± 1.6% in CL, p <0.05). The experiments with distal tubule MDCK culture cells demonstrated increased IDO expression after stimulation with TGF-β1(1.6 ± 0.1 units in control versus 3.1 ± 0.3 units in cells stimulated by TGF-β 1; p <0.05). Alpha-smooth muscle actin was expressed in cells stimulated by TGF-β1 and treatment with 1-MT potentiates its expression(24.8 ± 3.2% of αSMA+ cells in control, 40.1 ± 9.1% de of αSMA+ cells in MT, 58.8 ± 10.6% of αSMA+cells in TGF-β 1 and 66.1 ± 10.8% of αSMA+ cells in TGF-β 1 + MT; p <0.05 control versus TGF-β 1 + MT).. MDCK cells stimulated with TGF-β1 showed higher migration activity (wound assay), which was increased by treatment with MT(1.8 ± 0.2 mm2 in control, 1.4 ± 0.3 mm2 in MT, 2.8 ±0.1 mm2 in TGF-β 1 and 4.4 ± 0.3 mm2 in TGF-β 1 + MT; p <0.05 control versus TGF-β 1 and versus TGF-β 1 + MT). IDO is constitutively expressed in distal tubules and its expression increases during renal fibrogenesis. Although IDO can be induced by TGF-β1 in tubule cells, their chemical inhibitor acts as a pro-fibrotic agent, proposing the theory that IDO acts as a regulator of fibrogenic process.